2023
DOI: 10.3390/ijms24032067
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia Nanoparticles as Reinforcing Agents for Contemporary Dental Luting Cements: Physicochemical Properties and Shear Bond Strength to Monolithic Zirconia

Abstract: Nanofillers in resin materials can improve their mechanical and physicochemical properties. The present work investigated the effects of zirconia nanoparticles (NPs) as fillers in commercial dental luting cements. Two dual-cured self-adhesive composites and one resin modified glass ionomer (RMGI) luting cement were employed. Film thickness (FT), flexural strength (FS), water sorption (Wsp), and shear bond strength (SBS) to monolithic zirconia were evaluated according to ISO 16506:2017 and ISO 9917-2:2017, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In the present study, the obtained results for film thickness showed that all the tested groups present with film thickness less than 25 µm and thus meets the requirements of ISO 9917-1 standard (15) . The finding of the current research revealed that value of film thickness increased when the amount of added ZrO 2 NPs to the GIC cement increased and this increase in film thickness value was ZrO 2 NPs concentration dependent , this finding is similar to other studies (24,25,26) who found the same results and this may be due to a slight increase of the viscosity of the modified luting cement when compared to control group, which ultimately contribute to an increase of the film thickness (27,28) , also this increase in film thickness can be explained based on fact that small sized particles with less than 50 nm may results in increasing surface area of contact (28) or increase in the viscosity of the cement after addition of the nanoparticle (25) . Regarding compressive strength, the obtained results of the current study showed an improvement of the quality of compressive strength of the GICs following incorporation of ZrO 2 NPs when compared to the unmodified group.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the obtained results for film thickness showed that all the tested groups present with film thickness less than 25 µm and thus meets the requirements of ISO 9917-1 standard (15) . The finding of the current research revealed that value of film thickness increased when the amount of added ZrO 2 NPs to the GIC cement increased and this increase in film thickness value was ZrO 2 NPs concentration dependent , this finding is similar to other studies (24,25,26) who found the same results and this may be due to a slight increase of the viscosity of the modified luting cement when compared to control group, which ultimately contribute to an increase of the film thickness (27,28) , also this increase in film thickness can be explained based on fact that small sized particles with less than 50 nm may results in increasing surface area of contact (28) or increase in the viscosity of the cement after addition of the nanoparticle (25) . Regarding compressive strength, the obtained results of the current study showed an improvement of the quality of compressive strength of the GICs following incorporation of ZrO 2 NPs when compared to the unmodified group.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it was impossible to differentiate the materials by this parameter. Please note that an increase in impact strength could be achieved by loading PMMA with fibers or nanoparticles in various concentrations, but this would change the manufacturability of the materials, including the possibility of their AM processing [ 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The substance exhibits a decrease in bacterial adhesion and demonstrates minimal cytotoxic effects (Hu et al, 2019). ZrO 2 NPs have mechanical qualities and coloration comparable with that of a tooth, whereas also demonstrating low cytotoxicity, notable biocompatibility, and exceptional fracture resistance (Beketova et al, 2023). In the existing study, ZrO 2 AgDNPs demonstrated a wide range of shapes, encompassing both spherical and irregularly shaped polygonal crystals, as observed under SEM (Figure 1).…”
Section: Discussionmentioning
confidence: 99%